Classification of Omalisidae based on molecular data and morphology, with description of Paradrilinae subfam. nov. (Coleoptera: Elateroidea) - Kundrata, Robin; Baena, Manuel; Bocak, Ladislav (Zootaxa, 2015)
Omalisidae, a species-poor family of elateroid beetles, are distributed mostly in the Mediterranean region. The morphology of females is modified due to neotenic development and the males share some traits with other neotenic lineages in Elateroidea, namely Drilini (Elateridae: Agrypninae) and Lyropaeinae (Lycidae). A molecular phylogeny was inferred from six omalisid species representing four genera and the previously published dataset of Elateroidea. The DNA based phylogeny suggests that small-bodied males, reduced pronotal carinae and missing elytral costae evolved independently in multiple elateroid lineages. The limits of Omalisidae are redefined and seven genera, i.e., Omalisus Geoffroy, 1762, Phaeopterus Costa, 1857, Thilmanus Gemminger, 1869, Euanoma Reitter, 1889, Pseudeuanoma Pic, 1901, Paradrilus Kiesenwetter, 1865 and Cimbrion Kazantsev, 2010, are currently placed in the family. Thilmaninae Kazantsev, 2005 and Paradrilus Kiesenwetter, 1865 are transferred from Drilini (Elateridae: Agrypninae) to Omalisidae and the Paradrilinae subfam. nov. is proposed. Paradrilus differs from other Omalisidae in prolonged cranium, wide robust prosternum with two apical processes and absent sharp edge of the pronotum. The morphology of Paradrilus is described in detail, illustrated and all taxa currently classified in Omalisidae are listed.